PEMBENTUKAN WORD GRAPH PREPOSISI BAHASA INDONESIA MENGGUNAKAN METODE KNOWLEDGE GRAPH - Wulan Anggraeni (Faktor Exacta, 2010)
Knowledge Graph (KG) is a new method of knowledge representation, belongs to the category of semantics network. In principle, the composition of a knowledge graph is including concept and relationship. In KG we can expressed the meaning of word with word graph. Word graph is a graph contains concept and relationship to describe the meaning of word. In researched we expressed the meaning of preposition with word graph. Keyword: graph, knowledge graph, word graph, preposition.